Paleoecologic trends of Devonian Malvinokaffric fauna from the Paraná Basin as evidenced by trace fossils - Sedorko, Daniel; Netto, Renata Guimarães; Scheffler, Sandro Marcelo; Horodyski, Rodrigo Scalise; Bosetti, Elvio Pinto; Ghilardi, Renato Pirani [UNESP]; Mauller, Paula Mendlowicz; de Vargas, Mateus Rodrigues; Videira-Santos, Roberto; da Silva, Rafael Costa; Myzynski-Junior, Lucinei (Elsevier, 2021)
The Malvinokaffric Realm is an endemic paleogeographic region that inhabited Gondwanan high latitude seas during Early-Middle Devonian times. The causes for the collapse of this fauna are still debated but seem to be related to a transgressive event during Middle Devonian in the Chaco and Paraná basins in Bolivia and Brazil, which probably generated warmer water currents into the seas bearing Malvinokaffric fauna. This study applies ichnology as a relative proxy to better understand the impact of the main paleobiological events in the collapse of the Malvinokaffric Realm. Eight Devonian ichnoguilds are recognized in this study (Asterosoma, Glossifungites, Macaronichnus, Phycosiphon, Planolites, Skolithos, Teichichnus, and Zoophycos), and their stratigraphic distribution was compared with macrofossil distribution in Paraná Basin. The Pragian to Middle Emsian strata represent the climax of the diversity of body and trace fossils, recording distinct invertebrate life habits; the Asterosoma and Skolithos ichnoguilds predominate in the southern and northwestern borders, respectively, the last representing proximal settings. The “first decline” in Malvinokaffric diversity is diagnosed during the Eifelian, after an extensive regressive event during the late Emsian characterized by the reduction in different life habits, mostly suspension- and detritus-feeding. Trace fossils represent the Planolites ichnoguild principally, and the Eifelian strata are virtually absent on the northwest edge close to the paleo-basin flanks. The Givetian interval is characterized by the most expressive flooding event (Káčak event) that connected several Gondwanic basins, allowing the presence of extra-Malvinokaffric taxa in the Paraná Basin. Trace fossils are represented chiefly by the Phycosiphon ichnoguild in the Eifelian–Givetian boundary in the southern edge, and Planolites, Asterosoma, and Skolithos ichnoguilds in the upper strata. Finally, the Frasnian strata were diagnosed only to the northwestern edge of the basin, presenting a very low macrofossil diversity (e.g., lingulids and Australocoelia), and a low-ichnodiversity progradational trend from Phycosiphon to Skolithos ichnoguild. The identified paleoenvironmental changes evidences that the Early Devonian shallow seas (Jaguariaíva Member) were impacted by a gradual increase in freshwater input towards the Middle Devonian.
Keywords: Cruziana Ichnofacies; Devonian; Shale; Trace fossils; Zoophycos